DIFFERENCES IN FIRM FINANCIAL PERFORMANCE BEFORE AND DURING THE COVID-19: A STUDY ON FNB SECTOR - Suwondo, Lolyta Damayanti (Universitas Bunda Mulia, 2024)
Background: Covid-19 has had a major impact on the global economy, including in Indonesia. One of the most notable impacts has been felt by food and beverage firm. Indonesia government gives more attention for this sector due to its importance for public needs. This research is used to obtain the difference ROA ratio before and during Covid -19 period using statistical approach. This approach was chosen for finding is there a significant differences firm performance between before and during Covid-19 period.Objective: This approach was chosen for finding is there a significant differences firm performance between before and during Covid -19 period and analyze the differences.Research Methodology: Paired test approach for this research uses non-parametric Wilcoxon Ranks test by measuring return on assets (ROA). The population in this research were all firm operating in food an beverages sector from 2018-2021 which were listed on Indonesia for four consecutive years by classifying these four years in to before (2018-2019) and during Covid-19 (2020-2021).Research Findings: This research gained significantly different firm performance between before and during Covid-19. Wilcoxon Rank test performing this research gained a significant value 0.001<0.05. This difference is because the firm's ROA level tends to decline and suffer losses, the effect of implementing Perlakuan Pembatasan Kegiatan Masyarakat (PPKM) which seeks to reduce transmission through community mobility.Originality/Novelty of Research: This research provides a difference in firm financial performance with extended period data over two years before (2018-2019) and two years during Covid-19 (2020-2021).